Therapeutic effects of β-elemene via attenuation of the Wnt/β-catenin signaling pathway in cervical cancer cells - Wang, Lufang (Mol Med Rep, 2018)
Concurrent radio chemotherapy treatment prolongs the survival rate of patients with advanced cervical cancer; however, it has adverse side-effects. β-elemene, an active component of the traditional Chinese medicinal herb Curcuma zedoaria, is a promising alternative therapeutic drug for the treatment of advanced cervical cancer. The aim of the present study was to investigate the antitumor effects of β-elemene in human cervical cancer SiHa cells and to determine its underlying therapeutic molecular mechanisms. Cell viability, cell cycle progression and apoptosis were detected using an MTT assay and flow cytometry analysis. Furthermore, the levels of cell migration and cell invasion were investigated using Transwell and wound healing assays. The expression levels of Cyclin-dependent kinase inhibitor 2B (P15), Cyclin D1, cellular tumor antigen p53, apoptosis regulator Bcl-2 (Bcl-2), apoptosis regulator BAX (Bax), 72 kDa type IV collagenase (MMP-2), matrix metalloproteinase-9 (MMP-9), β-catenin, transcription factor 7 (TCF7), and Myc proto-oncogene protein (c-Myc) were analyzed via western blotting. The results revealed that β-elemene inhibited the proliferation of SiHa cells in a dose and time-dependent manner. Administration of β-elemene induced G1 phase cell-cycle arrest, as demonstrated by the upregulation of P15 expression and the downregulation of Cyclin D1 expression. Furthermore, the present study revealed that β-elemene induced apoptosis in SiHa cells by enhancing the expression of p53 and Bax, and suppressing the expression of Bcl-2. In addition, treatment with β-elemene inhibited cell migration and invasion via downregulation of MMP-2 and MMP-9 expression levels. Western blotting demonstrated that β-elemene reduced the expression levels of β-catenin and its downstream target molecule TCF7, thus resulting in reduced levels of their target proteins, including c-Myc, Cyclin D1, Bax and MMP-2 in cervical cancer cells. The results of the present study suggested that β-elemene may inhibit cell proliferation and invasion, in addition to inducing apoptosis, via attenuation of the Wnt/β-catenin signaling pathway in cervical cancer cells.